Cost effectiveness of treatment models of care for hepatitis C: the South Australian state-wide experience. Issue 10 (October 2020) - Ramachandran, Jeyamani; Kaambwa, Billingsley; Muller, Kate; Haridy, James; Tse, Edmund; Tilley, Emma; Altus, Rosalie; Waddell, Victoria; Gordon, David; Shaw, David; Huynh, Dep; Stewart, Jeffrey; et al.
Abstract : Aim: The objective was to study the long-term (lifetime) cost effectiveness of four different hepatitis C virus (HCV) treatment models of care (MOC) with directly acting antiviral drugs. Methods: A cohort Markov model-based probabilistic cost-effectiveness analysis (CEA) was undertaken extrapolating to up to 30 years from cost and outcome data collected from a primary study involving a real-life Australian cohort. In this study, noncirrhotic patients treated for HCV from 1 March 2016 to 28 February 2017 at four major public hospitals and liaising sites in South Australia were studied retrospectively. The MOC were classified depending on the person providing patient workup, treatment and monitoring into MOC1 (specialist), MOC2 (mixed specialist and hepatitis nurse), MOC3 (hepatitis nurse) and MOC4 (general practitioner, GP). Incremental costs were estimated from the Medicare perspective. Incremental outcomes were estimated based on the quality-adjusted life years (QALY) gained by achieving a sustained virological response. A cost-effectiveness threshold of Australian dollar 50 000 per QALY gained, the implicit criterion used for assessing the cost-effectiveness of new pharmaceuticals and medical services in Australia was assumed. Net monetary benefit (NMB) estimates based on this threshold were calculated. Results: A total of 1373 patients, 64% males, mean age 50 (SD ±11) years, were studied. In the CEA, MOC4 and MOC2 clearly dominated MOC1 over 30 years with lower costs and higher QALYs. Similarly, NMB was the highest in MOC4, followed by MOC2. Conclusion: Decentralized care using GP and mixed consultant nurse models were cost-effective ways of promoting HCV treatment uptake in the setting of unrestricted access to new antivirals.